2003
DOI: 10.1161/01.hyp.0000091822.00166.b1
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Overexpression of Renal LAT2 and Enhanced Tubular l -DOPA Uptake Precede the Onset of Hypertension

Abstract: Abstract-Spontaneously hypertensive rats (SHR) might have increased renal production of dopamine. L-3,4-Dihydroxyphenylalanine (L-DOPA) uptake in renal epithelial cells is promoted through the type 2 L-type amino acid transporter (LAT2), and this might rate-limit the synthesis of renal dopamine. The present study evaluated L-DOPA uptake in isolated renal proximal tubules of SHR and normotensive controls (Wistar-Kyoto rats [WKY]). Expression of LAT1 and LAT2 in the renal cortex and intestinal mucosa was also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…Studies on the inward transport of L-DOPA by tubular epithelial cells conducted in rat renal cortical slices (43) and cultured renal cell lines (16,55) demonstrated that uptake of L-DOPA is an active process, mediated through amino acid transporters. Recently, we reported that overexpression of type 2 Na ϩ -independent L-type amino acid transporter (LAT2) in the SHR kidney may contribute to the enhanced L-DOPA uptake (41). In line with these findings, immortalized renal proximal tubular epithelial cells from the SHR also overexpressed LAT2 (42).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Studies on the inward transport of L-DOPA by tubular epithelial cells conducted in rat renal cortical slices (43) and cultured renal cell lines (16,55) demonstrated that uptake of L-DOPA is an active process, mediated through amino acid transporters. Recently, we reported that overexpression of type 2 Na ϩ -independent L-type amino acid transporter (LAT2) in the SHR kidney may contribute to the enhanced L-DOPA uptake (41). In line with these findings, immortalized renal proximal tubular epithelial cells from the SHR also overexpressed LAT2 (42).…”
supporting
confidence: 55%
“…Recently, we demonstrated that overexpression of LAT2 in SHR kidney is organ specific, precedes the onset of hypertension, and is accompanied by enhanced ability to take up L-DOPA (41). This led to the suggestion that overexpression of renal LAT2 may constitute the basis for the enhanced renal production of dopamine in the SHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The inhibitory effect of dopamine on Na ϩ -K ϩ -ATPase is influenced by intracellular sodium and calcium; dopamine inhibits Na (86,164,165). L-DOPA is the sole source of renal tubular dopamine production.…”
Section: Renal Dopamine Receptorsmentioning
confidence: 99%
“…Salt loading can also increase in AADC activity in proximal tubules (86). In spontaneously hypertensive rats (SHR), sodium-dependent and LAT-1 L-DOPA uptake may also participate and may explain, in part, the increased dopamine synthesis in SHRs (164,170). Saline loading may also be associated with decreased renal degradation of dopamine by catechol-o-methyl transferase (COMT) (152) to 3-methoxytyramine (3MT) and eventually to homovanillic acid (HVA).…”
Section: Renal Dopamine Receptorsmentioning
confidence: 99%